Hindered Trench Migration Due To Slab Steepening Controls the Formation of the Central Andes. Issue 12 (8th December 2022) - Pons, Michaël; Sobolev, Stephan V.; Liu, Sibiao; Neuharth, Derek
Abstract: The formation of the Central Andes dates back to ∼50 Ma, but its most pronounced episode, including the growth of the Altiplano‐Puna Plateau and pulsatile tectonic shortening phases, occurred within the last 25 Ma. The reason for this evolution remains unexplained. Using geodynamic numerical modeling we infer that the primary cause of the pulses of tectonic shortening and growth of the Central Andes is the changing geometry of the subducted Nazca plate, and particularly the steepening of the mid‐mantle slab segment which results in a slowing down of the trench retreat and subsequent increase in shortening of the advancing South America plate. This steepening first happens after the end of the flat slab episode at ∼25 Ma, and later during the buckling and stagnation of the slab in the mantle transition zone. Processes that mechanically weaken the lithosphere of the South America plate, as suggested in previous studies, enhance the intensity of the shortening events. These processes include delamination of the mantle lithosphere and weakening of foreland sediments. Our new modeling results are consistent with the timing and amplitude of the deformation from geological data in the Central Andes at the Altiplano latitude. Plain Language Summary: The Central Andes is a subduction‐type orogeny that formed as a result of the interaction between the Nazca oceanic plate and the South American continental plate over the last 50 million years. Growth of the Andes is primarily the result of crustal shortening. Nevertheless, "geological" data compiled from previous studies have shown that phases of drastic pulsatile shortening occur at 15 and 5 Ma. In this study, we used high‐resolution 2D numerical geodynamic simulations to investigate the link between oceanic and continental plate dynamics and their interaction. We find that when the oceanic plate steepens in the mantle transition zone, the trench retreat is hindered. Coupled with the weakening of the continental plate through the slab flattening and subsequent delamination of the lithospheric mantle, this leads to pulsatile shortening phases of a magnitude equivalent to that suggested by the data. Key Points: The steepening of the slab due to slab buckling hinders the trench retreating and explains the main pulsatile phases of the deformation during the last 25 Ma The absolute motion of the overriding plate controls the regime of subduction dynamics Flat slab and eclogitization are required to weaken and then shorten the overriding plate when the slab steepens and the trench is hindered